Biodiversity and Wine, a Nice Wedding: Saumur–Champigny in the Varinelles Domaine (Loire Valley, France). (June 2013) - Noblet, Jean-Pierre; Pesqueux, Yvon; Simon, Eric
Since 2004, the 130 winegrowers of the Saumur–Champigny appellation d'origine controlee have been committed to biodiversity. In a sector sometimes resistant to change, and indeed for the first time in France, winegrowers have chosen more ecological weed control methods and concentrated on creating and maintaining plant hedges within zones écologiques reservoirs (ecological conservation areas)(ZER) (Jarno, 2011 ). The growers' Syndicate, backed by a powerful regional cooperative, rallied all its members and urged them to commit to the process. Collective awareness has driven the majority of winegrowers to 'go organic' and with the ultimate benefit of being awarded an organic label. But going organic is costly in terms of time, labour and finances and inevitably increases production costs. However, despite the less favourable cost equation, their business model is nonetheless effective, and most producers manage to sell their entire product. The aim of this case study is to show how some wine producers, in the quest for quality, have 'looked outside the box' for new information (for example: sustainable agriculture, biodiversity, biodynamics), assimilated that information and applied it to their own operation and production for improved commercial results.